Paving the Way for Speech: Voice-Training-Induced Plasticity in Chronic Aphasia and Apraxia of Speech—Three Single Cases - Monika Jungblut; Walter Huber; Christiane Mais; Ralph Schnitker (Neural Plasticity)
Difficulties with temporal coordination or sequencing of speech movements are frequently reported in aphasia patients with concomitant apraxia of speech (AOS). Our major objective was to investigate the effects of specific rhythmic-melodic voice training on brain activation of those patients. Three patients with severe chronic nonfluent aphasia and AOS were included in this study. Before and after therapy, patients underwent the same fMRI procedure as 30 healthy control subjects in our prestudy, which investigated the neural substrates of sung vowel changes in untrained rhythm sequences. A main finding was that post-minus pretreatment imaging data yielded significant perilesional activations in all patients for example, in the left superior temporal gyrus, whereas the reverse subtraction revealed either no significant activation or right hemisphere activation. Likewise, pre- and posttreatment assessments of patients’ vocal rhythm production, language, and speech motor performance yielded significant improvements for all patients. Our results suggest that changes in brain activation due to the applied training might indicate specific processes of reorganization, for example, improved temporal sequencing of sublexical speech components. In this context, a training that focuses on rhythmic singing with differently demanding complexity levels as concerns motor and cognitive capabilities seems to support paving the way for speech.